2020
DOI: 10.1016/j.celrep.2020.107782
|View full text |Cite
|
Sign up to set email alerts
|

NeuroD1 Dictates Tumor Cell Differentiation in Medulloblastoma

Abstract: SUMMARY Tumor cells are characterized by unlimited proliferation and perturbed differentiation. Using single-cell RNA sequencing, we demonstrate that tumor cells in medulloblastoma (MB) retain their capacity to differentiate in a similar way as their normal originating cells, cerebellar granule neuron precursors. Once they differentiate, MB cells permanently lose their proliferative capacity and tumorigenic potential. Differentiated MB cells highly express NeuroD1, a helix-loop-helix transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 68 publications
4
30
0
Order By: Relevance
“…Functional analyses of the molecular pathways driving differentiation toward the SHH-C2 is feasible now that this subpopulation has been molecularly defined and may reveal therapeutically relevant insights. This approach can explored by application of scRNA-seq to in vivo GEM models, that we and others have shown to recapitulate the cellular heterogeneity of SHH MB (Cheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Functional analyses of the molecular pathways driving differentiation toward the SHH-C2 is feasible now that this subpopulation has been molecularly defined and may reveal therapeutically relevant insights. This approach can explored by application of scRNA-seq to in vivo GEM models, that we and others have shown to recapitulate the cellular heterogeneity of SHH MB (Cheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…6 However, no difference in the NeuroD1 methylation was observed between differentiated MB cells and bulk tumor cells (Tag1-). 4 By ChIP-PCR experiments, we found that the regulatory region of NeuroD1 was more enriched with histone trimethylation of H3K27 in differentiated MB cells, compared with that in bulk MB cells, suggesting that NeuroD1 expression in bulk tumor cells may be repressed by trimethylation of histone 3 lysine-27 (H3K27me3). EZH2 is a catalytic subunit of PRC2 complex, mediating the histone trimethylation of H3K27.…”
mentioning
confidence: 89%
“…Recently our group revealed that a proportion of tumor cells in human and mouse Hh-MB became differentiated based on single cell RNA sequencing. 4 Those differentiated cells highly expressed genes associated with neuronal maturation and differentiation including Cntn2, Pax6, NeuroD1, Tubb3, and Gap43. Immunohistochemistry revealed that differentiated MB cells were exclusively negative for Ki67, suggesting that those tumor cells have stopped dividing after becoming differentiated.…”
mentioning
confidence: 99%
“…Following this principle, inhibition of N-MYC in MYCN-amplified neuroblastoma cell lines induced a differentiation morphology as well as upregulation of neural differentiation genes (Kang et al, 2006;Henriksen et al, 2011;Jiang et al, 2011;Westermark et al, 2011;Hossain et al, 2013). Differentiation phenotypes were also observed upon genetic manipulation of medulloblastoma models (Liu et al, 2017;Cheng et al, 2020;Zagozewski et al, 2020), and MRT models (Betz et al, 2002;Nakayama et al, 2017;Wang et al, 2017). These studies show that reversal of the genetic driver can transform tumor cells to a more mature cell state, possibly reflecting the matured cell type it would have become, had it not become cancerous.…”
Section: Reverse Tumor Modeling and Differentiation Therapymentioning
confidence: 79%